Effect of lattice strain on stabilization temperature of calcium added (Mg, Co, Ni, Cu, Zn)O - Gautam A.; Ahmad M.I. (My University, 2025)
The effect of lattice strain due to relatively larger isovalent cation substitution on the stability landscape of equiatomic (Mg, Co, Ni, Cu, Zn)O high entropy oxide is explored. A simple yet effective formulation to incorporate strain energy for calculating critical temperature for high entropy single-phase rocksalt phase formation is proposed. The estimated phase stabilization temperature is successfully validated for varying substitution calcium (x = 0.05, 0.1, 0.16) in (Co, Mg, Ni, Cu, Zn)1-xCaxO. We used XRD and electron microscopy to confirm the single-phase formation of rocksalt HEOs. © 2025